Third Space Network: Theatrical Roots - Packer, Randall (Lumina, 2017)
This essay provides an overview of artistic work and experimentation leading to the concept of the Third Space Network: a live Internet broadcast and performance project for connecting artists, audiences, and cultural perspectives from around the world. The concept of the third space suggests the collapse of the local (first space) and remote (second space) into a third, socially constructed networked space. The third space can be viewed as a new realization of the community of theater in a globally connected culture: performance space for broadcasted live art, a forum for the aggregation of artist streams of media art, and an arena for social interaction. The following is a personal artistic history and contextualization of nearly thirty years of live performance, interactive media, installation, Internet art, and the spaces they inhabit. This essay connects early work in Music Theater from the late 1980s and early 1990s to more recent networked projects to frame the idea of the Third Space Network as a new theatrical environment rich in potential for live performance and creative discourse.